Skip to content
🎉 DeepSeek-R1 đŸĨŗ
❓The scale of a plane map is 1:500. Is the ratio of the area of the figure on the map to the actual area 1:500... (True or False)?

💡First, I need to understand what the scale of 1:500 means. This indicates that 1 unit on the map corresponds to 500 units in reality.Next, I should consider how this scale affects areas. Since area is a two-dimensional measurement, the scale factor for area would be the square of the linear scale factor.Calculating the area scale factor, I square the linear scale factor: (500^2 = 250,000).Therefore, the ratio of the area on the map to the actual area is 1:250,000, not 1:500.

❓Garbage classification refers to a series of activities in which garbage is classified, stored, disposed of, and transported according to certain regulations or standards, so as to transform it into a public resource. It is the duty of every citizen to do a good job in garbage classification. It is known that the decomposition rate v of a certain type of garbage approximately satisfies the relationship v=acdot b^{t} (where a and b are positive constants) with time t (in months). After 6 months, the decomposition rate of this type of garbage is 5%, and after 12 months, the decomposition rate is 10%. Approximately how many months does it take for this type of garbage to completely decompose?A: 20B: 28C: 32D: 40

💡Alright, so I have this problem about garbage decomposition rates. It says that the decomposition rate v of a certain type of garbage follows the relationship v = a * b^t, where a and b are positive constants, and t is time in months. After 6 months, the decomposition rate is 5%, and after 12 months, it's 10%. I need to figure out approximately how many months it takes for the garbage to completely decompose. The options are 20, 28, 32, or 40 months.Okay, let's break this down. First, I know that the decomposition rate is modeled by an exponential function, v = a * b^t. So, it's an exponential growth or decay model. Given that decomposition rates increase over time, I think it's an exponential growth model, but I should keep in mind that it might be a decay if the rate decreases, but in this case, it's increasing from 5% to 10%, so it's definitely growth.We have two data points: at t = 6 months, v = 5% (which is 0.05), and at t = 12 months, v = 10% (which is 0.1). So, plugging these into the equation, we get two equations:1. 0.05 = a * b^62. 0.1 = a * b^12I need to solve for a and b first. Maybe I can divide the second equation by the first to eliminate a. Let's try that:(0.1) / (0.05) = (a * b^12) / (a * b^6)Simplifying the left side: 0.1 / 0.05 = 2.On the right side: (a / a) cancels out, and b^12 / b^6 = b^(12-6) = b^6.So, 2 = b^6.To solve for b, I can take the sixth root of both sides:b = 2^(1/6)Hmm, 2^(1/6) is approximately... Well, 2^(1/6) is the same as the sixth root of 2. I know that 2^(1/3) is about 1.26, so 2^(1/6) would be the square root of that, which is roughly 1.1225. Let me double-check that with a calculator:2^(1/6) ≈ e^(ln(2)/6) ≈ e^(0.10536) ≈ 1.1107. Okay, so approximately 1.1107.So, b ≈ 1.1107.Now, let's find a using one of the original equations. Let's use the first one:0.05 = a * b^6We know that b^6 = 2, so:0.05 = a * 2Therefore, a = 0.05 / 2 = 0.025.So, now we have a = 0.025 and b ≈ 1.1107.Therefore, the decomposition rate equation is:v = 0.025 * (1.1107)^tNow, the question is asking when the garbage completely decomposes. I assume that means when the decomposition rate v reaches 100%, which is v = 1.So, set v = 1:1 = 0.025 * (1.1107)^tWe need to solve for t.First, divide both sides by 0.025:(1.1107)^t = 1 / 0.025 = 40So, (1.1107)^t = 40To solve for t, we can take the natural logarithm of both sides:ln((1.1107)^t) = ln(40)Using the logarithm power rule, ln(a^b) = b * ln(a):t * ln(1.1107) = ln(40)Therefore, t = ln(40) / ln(1.1107)Let me compute ln(40) and ln(1.1107):ln(40) ≈ 3.6889ln(1.1107) ≈ 0.10536So, t ≈ 3.6889 / 0.10536 ≈ 35.01 months.Wait, that's approximately 35 months, but the options are 20, 28, 32, or 40. 35 is closest to 32 or 40. Hmm, maybe my approximation of b was a bit off. Let me check the calculations again.Wait, I approximated b as 1.1107, but actually, 2^(1/6) is exactly equal to e^(ln(2)/6). Let me compute ln(2)/6:ln(2) ≈ 0.6931So, ln(2)/6 ≈ 0.1155Therefore, b = e^(0.1155) ≈ 1.1225Wait, earlier I thought 2^(1/6) was approximately 1.1107, but actually, it's about 1.1225. Let me recalculate with this more accurate value.So, b ≈ 1.1225Now, let's recalculate a:From 0.05 = a * b^6But b^6 = 2, so a = 0.05 / 2 = 0.025, same as before.So, the equation is v = 0.025 * (1.1225)^tSet v = 1:1 = 0.025 * (1.1225)^tDivide both sides by 0.025:(1.1225)^t = 40Take natural logs:ln(1.1225^t) = ln(40)t * ln(1.1225) = ln(40)Compute ln(1.1225):ln(1.1225) ≈ 0.1155ln(40) ≈ 3.6889So, t ≈ 3.6889 / 0.1155 ≈ 31.94 months.Ah, that's approximately 32 months. So, the answer should be 32 months, which is option C.Wait, but earlier I thought it was 35, but that was because I had a less accurate value for b. So, with a more accurate b, it comes out to approximately 32 months.Let me double-check the calculations once more to be sure.Given:v = a * b^tAt t = 6, v = 0.05At t = 12, v = 0.1So, 0.05 = a * b^60.1 = a * b^12Divide the second equation by the first:0.1 / 0.05 = (a * b^12) / (a * b^6)2 = b^6So, b = 2^(1/6) ≈ 1.1225Then, a = 0.05 / (b^6) = 0.05 / 2 = 0.025So, v = 0.025 * (1.1225)^tSet v = 1:1 = 0.025 * (1.1225)^t(1.1225)^t = 40Take natural logs:t = ln(40) / ln(1.1225) ≈ 3.6889 / 0.1155 ≈ 31.94 ≈ 32 months.Yes, that seems consistent. So, the answer is 32 months, which is option C.

❓A 2times 4 rectangle and a 4times 5 rectangle are contained within a square without overlapping at any interior point, and the sides of the square are parallel to the sides of the two given rectangles. What is the smallest possible area of the square?

💡To determine the smallest square that can contain both a (2 times 4) rectangle and a (4 times 5) rectangle without overlapping and with sides parallel to the square, we need to consider different possible arrangements of the rectangles within the square.First, let's consider the dimensions of the rectangles:- The (2 times 4) rectangle has a width of 2 units and a length of 4 units.- The (4 times 5) rectangle has a width of 4 units and a length of 5 units.We need to find the smallest square such that both rectangles can fit inside without overlapping. The side length of the square must be at least as large as the largest dimension of the rectangles or the sum of certain dimensions if the rectangles are placed side by side.Let's explore different arrangements:1. **Placing the rectangles side by side horizontally:** - The total width would be (4 + 5 = 9) units. - The height would be the maximum of 2 and 4, which is 4 units. - This arrangement would require a square of side length 9, which is larger than necessary.2. **Placing the rectangles side by side vertically:** - The total height would be (2 + 4 = 6) units. - The width would be the maximum of 4 and 5, which is 5 units. - This arrangement would require a square of side length 6, which is still larger than necessary.3. **Stacking the rectangles in a more efficient manner:** - Place the (2 times 4) rectangle in one corner of the square. - Place the (4 times 5) rectangle in an adjacent corner. - The side length of the square needs to accommodate both the length and width of the rectangles without overlap.After considering various configurations, the most efficient arrangement is to place the (2 times 4) rectangle and the (4 times 5) rectangle such that their longer sides are aligned with the sides of the square, and they do not overlap. This results in the side length of the square being 7 units, as it can accommodate both rectangles without exceeding the square's boundaries.Therefore, the smallest possible area of the square is (7^2 = 49) square units.

❓Given the inequality ax^{2}+left(1-2aright)x-2 gt 0, ain R. (1) If the solution set of the inequality is {xleft|right.x lt -1 or x gt 2}, find the value of a; (2) Discuss the solution set of the inequality for ain R.

💡Okay, so I have this inequality: ( ax^2 + (1 - 2a)x - 2 > 0 ). And I need to solve two parts. First, find the value of ( a ) when the solution set is ( {x | x < -1 text{ or } x > 2} ). Second, discuss the solution set for all real numbers ( a ).Starting with part (1). The solution set given is ( x < -1 ) or ( x > 2 ). That means the quadratic equation ( ax^2 + (1 - 2a)x - 2 = 0 ) has roots at ( x = -1 ) and ( x = 2 ). So, these are the points where the quadratic equals zero, and the inequality is positive outside this interval.Since ( -1 ) and ( 2 ) are roots, I can use the fact that for a quadratic equation ( ax^2 + bx + c = 0 ), the sum of the roots is ( -b/a ) and the product is ( c/a ).Let me write that down:Sum of roots: ( -1 + 2 = 1 = -frac{1 - 2a}{a} )Product of roots: ( (-1)(2) = -2 = frac{-2}{a} )So, from the product of roots: ( -2 = frac{-2}{a} ). Let me solve this for ( a ).Multiply both sides by ( a ): ( -2a = -2 )Divide both sides by -2: ( a = 1 )Wait, let me check the sum of roots as well to make sure.Sum of roots: ( 1 = -frac{1 - 2a}{a} )Substitute ( a = 1 ): ( 1 = -frac{1 - 2(1)}{1} = -frac{-1}{1} = 1 ). That checks out.So, ( a = 1 ) is correct.Moving on to part (2). I need to discuss the solution set for all real numbers ( a ).First, let's factor the quadratic if possible. The quadratic is ( ax^2 + (1 - 2a)x - 2 ). Let me try to factor it.Looking for two numbers that multiply to ( a times (-2) = -2a ) and add up to ( 1 - 2a ). Hmm, maybe it's easier to factor by grouping.Let me rewrite the quadratic:( ax^2 + (1 - 2a)x - 2 )Let me group the first two terms and the last two terms:( (ax^2 + (1 - 2a)x) + (-2) )Factor out ( x ) from the first group:( x(ax + 1 - 2a) - 2 )Hmm, not sure if that helps. Maybe another approach. Let me try to factor it as ( (ax + m)(x + n) ).Expanding ( (ax + m)(x + n) = ax^2 + (an + m)x + mn )Comparing coefficients:1. ( ax^2 + (an + m)x + mn = ax^2 + (1 - 2a)x - 2 )So, we have:- ( an + m = 1 - 2a )- ( mn = -2 )We need to find integers ( m ) and ( n ) such that ( mn = -2 ). Possible pairs are (1, -2), (-1, 2), (2, -1), (-2, 1).Let me try ( m = 1 ) and ( n = -2 ):Then, ( an + m = a(-2) + 1 = -2a + 1 ). Comparing to ( 1 - 2a ), which is the same. Perfect!So, the quadratic factors as ( (ax + 1)(x - 2) ).So, ( ax^2 + (1 - 2a)x - 2 = (ax + 1)(x - 2) ).Great, now the inequality becomes ( (ax + 1)(x - 2) > 0 ).Now, to solve this inequality, we need to consider the critical points where each factor is zero: ( x = -frac{1}{a} ) and ( x = 2 ). The sign of the expression depends on the intervals determined by these critical points.But before that, we need to consider different cases based on the value of ( a ).Case 1: ( a = 0 )If ( a = 0 ), the quadratic becomes ( 0x^2 + (1 - 0)x - 2 = x - 2 ). So, the inequality is ( x - 2 > 0 ), which simplifies to ( x > 2 ). So, the solution set is ( (2, infty) ).Case 2: ( a neq 0 )We have two critical points: ( x = -frac{1}{a} ) and ( x = 2 ). The order of these points depends on the value of ( a ).Let's analyze the critical points:- If ( a > 0 ), then ( -frac{1}{a} ) is negative, so ( -frac{1}{a} < 2 ).- If ( a < 0 ), then ( -frac{1}{a} ) is positive. Depending on the magnitude, ( -frac{1}{a} ) could be greater or less than 2.So, let's break it down further.Subcase 2.1: ( a > 0 )Here, ( -frac{1}{a} < 2 ). The critical points divide the real line into three intervals:1. ( (-infty, -frac{1}{a}) )2. ( (-frac{1}{a}, 2) )3. ( (2, infty) )We need to test the sign of ( (ax + 1)(x - 2) ) in each interval.- For ( x < -frac{1}{a} ): Let's pick ( x = -frac{2}{a} ). Then, ( ax + 1 = a(-frac{2}{a}) + 1 = -2 + 1 = -1 ). ( x - 2 = -frac{2}{a} - 2 ). Since ( a > 0 ), ( -frac{2}{a} ) is negative, so ( x - 2 ) is negative. Multiplying two negatives gives positive. So, the expression is positive.- For ( -frac{1}{a} < x < 2 ): Let's pick ( x = 0 ). Then, ( ax + 1 = 1 ). ( x - 2 = -2 ). Multiplying positive and negative gives negative. So, the expression is negative.- For ( x > 2 ): Let's pick ( x = 3 ). Then, ( ax + 1 = 3a + 1 ) (positive since ( a > 0 )). ( x - 2 = 1 ) (positive). Multiplying two positives gives positive. So, the expression is positive.Therefore, the solution set is ( (-infty, -frac{1}{a}) cup (2, infty) ).Subcase 2.2: ( a < 0 )Here, ( -frac{1}{a} ) is positive. We need to compare ( -frac{1}{a} ) with 2.Subsubcase 2.2.1: ( -frac{1}{a} > 2 )This happens when ( -frac{1}{a} > 2 ) => ( -1 > 2a ) (since ( a < 0 ), multiplying both sides reverses the inequality) => ( a > -frac{1}{2} ). But since ( a < 0 ), this is ( -frac{1}{2} < a < 0 ).So, the critical points are ( x = 2 ) and ( x = -frac{1}{a} ), with ( 2 < -frac{1}{a} ).The intervals are:1. ( (-infty, 2) )2. ( (2, -frac{1}{a}) )3. ( (-frac{1}{a}, infty) )Testing the sign:- For ( x < 2 ): Let's pick ( x = 0 ). ( ax + 1 = 1 ) (positive). ( x - 2 = -2 ) (negative). Product is negative.- For ( 2 < x < -frac{1}{a} ): Let's pick ( x = frac{2 + (-frac{1}{a})}{2} ). Wait, maybe a better approach. Let's pick ( x = 3 ) if ( -frac{1}{a} > 3 ), but actually, since ( -frac{1}{a} > 2 ), let's pick ( x = frac{3}{2} ) if ( -frac{1}{a} > frac{3}{2} ). Hmm, maybe it's better to pick a specific value. Let me choose ( x = 3 ) if ( -frac{1}{a} > 3 ), otherwise, pick something else. Alternatively, let's analyze the sign.Since ( a < 0 ), ( ax + 1 ) is a line with negative slope. At ( x = 2 ), ( ax + 1 = 2a + 1 ). Since ( a > -frac{1}{2} ), ( 2a + 1 > 2(-frac{1}{2}) + 1 = -1 + 1 = 0 ). So, at ( x = 2 ), ( ax + 1 > 0 ). Then, as ( x ) increases beyond 2, ( ax + 1 ) decreases because ( a < 0 ). At ( x = -frac{1}{a} ), ( ax + 1 = 0 ). So, between ( x = 2 ) and ( x = -frac{1}{a} ), ( ax + 1 ) is positive, and ( x - 2 ) is positive. So, the product is positive.For ( x > -frac{1}{a} ): ( ax + 1 ) becomes negative (since ( a < 0 ) and ( x > -frac{1}{a} )), and ( x - 2 ) is positive. So, the product is negative.Therefore, the solution set is ( (2, -frac{1}{a}) ).Subsubcase 2.2.2: ( -frac{1}{a} = 2 )This occurs when ( -frac{1}{a} = 2 ) => ( a = -frac{1}{2} ).In this case, the quadratic becomes ( -frac{1}{2}x^2 + (1 - 2(-frac{1}{2}))x - 2 = -frac{1}{2}x^2 + (1 + 1)x - 2 = -frac{1}{2}x^2 + 2x - 2 ).Let me factor this: ( -frac{1}{2}x^2 + 2x - 2 = -frac{1}{2}(x^2 - 4x + 4) = -frac{1}{2}(x - 2)^2 ).So, the inequality becomes ( -frac{1}{2}(x - 2)^2 > 0 ). Since ( (x - 2)^2 ) is always non-negative, multiplying by ( -frac{1}{2} ) makes it non-positive. So, the inequality ( -frac{1}{2}(x - 2)^2 > 0 ) has no solution. Therefore, the solution set is empty.Subsubcase 2.2.3: ( -frac{1}{a} < 2 )This happens when ( -frac{1}{a} < 2 ) => ( -1 < 2a ) (since ( a < 0 ), multiplying both sides reverses the inequality) => ( a > -frac{1}{2} ). Wait, but in this subcase, ( a < 0 ) and ( -frac{1}{a} < 2 ), which implies ( a < -frac{1}{2} ).So, ( a < -frac{1}{2} ).The critical points are ( x = -frac{1}{a} ) and ( x = 2 ), with ( -frac{1}{a} < 2 ).The intervals are:1. ( (-infty, -frac{1}{a}) )2. ( (-frac{1}{a}, 2) )3. ( (2, infty) )Testing the sign:- For ( x < -frac{1}{a} ): Let's pick ( x = -frac{2}{a} ). ( ax + 1 = a(-frac{2}{a}) + 1 = -2 + 1 = -1 ). ( x - 2 = -frac{2}{a} - 2 ). Since ( a < 0 ), ( -frac{2}{a} ) is positive. So, ( x - 2 ) could be positive or negative depending on ( a ). Wait, actually, since ( -frac{1}{a} < 2 ), ( a < -frac{1}{2} ). So, ( -frac{2}{a} ) is less than 4 because ( a < -frac{1}{2} ) implies ( -frac{2}{a} < 4 ). So, ( x = -frac{2}{a} ) is less than 4, but more importantly, ( x - 2 ) is ( -frac{2}{a} - 2 ). Since ( a < -frac{1}{2} ), ( -frac{2}{a} ) is positive and less than 4. So, ( x - 2 ) could be positive or negative. Hmm, maybe a better approach is to analyze the sign.Since ( a < 0 ), ( ax + 1 ) is a line with negative slope. At ( x = -frac{1}{a} ), ( ax + 1 = 0 ). For ( x < -frac{1}{a} ), ( ax + 1 > 0 ) (since the line is above zero to the left of the root). ( x - 2 ) is negative because ( x < -frac{1}{a} < 2 ). So, positive times negative is negative.For ( -frac{1}{a} < x < 2 ): ( ax + 1 ) is negative (since ( x > -frac{1}{a} )), and ( x - 2 ) is negative. Negative times negative is positive.For ( x > 2 ): ( ax + 1 ) is negative (since ( a < 0 ) and ( x > 2 > -frac{1}{a} )), and ( x - 2 ) is positive. Negative times positive is negative.Therefore, the solution set is ( (-frac{1}{a}, 2) ).Putting it all together:- If ( a > 0 ), solution set is ( (-infty, -frac{1}{a}) cup (2, infty) ).- If ( a = 0 ), solution set is ( (2, infty) ).- If ( -frac{1}{2} < a < 0 ), solution set is ( (2, -frac{1}{a}) ).- If ( a = -frac{1}{2} ), solution set is empty.- If ( a < -frac{1}{2} ), solution set is ( (-frac{1}{a}, 2) ).I think that covers all cases for ( a ).

❓Tom, Dorothy, and Sammy went on a vacation and agreed to split the costs evenly. During their trip, Tom paid 150, Dorothy paid 160, and Sammy paid 210. To equalize the costs, Tom gave Sammy t dollars, Dorothy gave Sammy d dollars, and Sammy gave s dollars to Dorothy. What is t-d+s?textbf{(A)} 10qquadtextbf{(B)} 15qquadtextbf{(C)} 20qquadtextbf{(D)} 25qquadtextbf{(E)} 30

💡First, calculate the total amount paid by all three individuals:[150 + 160 + 210 = 520]Next, determine the amount each person should have paid to split the costs evenly:[frac{520}{3} approx 173.33]Calculate how much each person needs to adjust:- Tom paid 150, which is 173.33 - 150 = 23.33 less than he should have paid.- Dorothy paid 160, which is 173.33 - 160 = 13.33 less than she should have paid.- Sammy paid 210, which is 210 - 173.33 = 36.67 more than he should have paid.Assume payments to offset balances:- Tom owes Sammy 23.33.- Dorothy owes Sammy 13.33.- Sammy gives s = 10 dollars to Dorothy.Calculate the new value of ( t - d + s ):[t - d + s = 23.33 - 13.33 + 10 = 20]Thus, the value of ( t - d + s ) is ( 20 ).

❓The following line is parameterized, so that its direction vector is of the form begin{pmatrix} 3 b end{pmatrix}. Find b.[asy]unitsize(0.4 cm);pair A, B, L, R;int i, n;for (i = -8; i <= 8; ++i) { draw((i,-8)--(i,8),gray(0.7)); draw((-8,i)--(8,i),gray(0.7));}draw((-8,0)--(8,0),Arrows(6));draw((0,-8)--(0,8),Arrows(6));A = (-3,3);B = A + (4,3);L = extension(A, B, (-8,0), (-8,1));R = extension(A, B, (0,8), (1,8));draw(L--R, red);label("x", (8,0), E);label("y", (0,8), N);[/asy]

💡Alright, so I have this problem here where I need to find the value of ( b ) in the direction vector ( begin{pmatrix} 3 b end{pmatrix} ) for a given line. The problem also includes an Asymptote figure, which I can't see directly, but based on the description, it's a coordinate plane with a red line drawn. The line passes through two specific points, which are given in the solution as ( begin{pmatrix} -3 3 end{pmatrix} ) and ( begin{pmatrix} 1 6 end{pmatrix} ). First, I need to understand what a direction vector is. From what I remember, a direction vector of a line is a vector that points in the direction of the line. It can be found by subtracting the coordinates of two points on the line. So, if I have two points ( A ) and ( B ) on the line, the direction vector ( vec{AB} ) is ( B - A ).Looking at the given points, ( A = (-3, 3) ) and ( B = (1, 6) ). To find the direction vector, I subtract the coordinates of ( A ) from ( B ):[vec{AB} = begin{pmatrix} 1 - (-3) 6 - 3 end{pmatrix} = begin{pmatrix} 4 3 end{pmatrix}]So, the direction vector is ( begin{pmatrix} 4 3 end{pmatrix} ). But the problem asks for a direction vector of the form ( begin{pmatrix} 3 b end{pmatrix} ). This means I need to scale the direction vector ( begin{pmatrix} 4 3 end{pmatrix} ) so that the ( x )-component becomes 3 instead of 4.Scaling a vector means multiplying it by a scalar. Let's call this scalar ( k ). So, if I multiply the direction vector by ( k ), I should get a new vector where the ( x )-component is 3:[k times begin{pmatrix} 4 3 end{pmatrix} = begin{pmatrix} 3 b end{pmatrix}]This gives me two equations:1. ( 4k = 3 )2. ( 3k = b )From the first equation, I can solve for ( k ):[k = frac{3}{4}]Now, substituting this value of ( k ) into the second equation to find ( b ):[b = 3k = 3 times frac{3}{4} = frac{9}{4}]So, ( b = frac{9}{4} ). Wait, let me double-check my work. The direction vector is indeed found by subtracting the coordinates of the two points, which gives ( begin{pmatrix} 4 3 end{pmatrix} ). Scaling this vector to have an ( x )-component of 3 requires multiplying by ( frac{3}{4} ), which scales both components. Multiplying 3 by ( frac{3}{4} ) does give ( frac{9}{4} ). That seems correct.Alternatively, I can think about the slope of the line. The slope ( m ) is given by the change in ( y ) over the change in ( x ), which is ( frac{3}{4} ). The direction vector ( begin{pmatrix} 3 b end{pmatrix} ) should have the same slope, so ( frac{b}{3} = frac{3}{4} ). Solving for ( b ) gives ( b = frac{9}{4} ), which matches my previous result.I think I'm confident that ( b = frac{9}{4} ) is the correct answer.**Final Answer**The value of ( b ) is boxed{dfrac{9}{4}}.

Released under the MIT License.

has loaded